2005
DOI: 10.1038/nature04474
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptors mediate calcium accumulation in myelin during chemical ischaemia

Abstract: Central nervous system myelin is a specialized structure produced by oligodendrocytes that ensheaths axons, allowing rapid and efficient saltatory conduction of action potentials. Many disorders promote damage to and eventual loss of the myelin sheath, which often results in significant neurological morbidity. However, little is known about the fundamental mechanisms that initiate myelin damage, with the assumption being that its fate follows that of the parent oligodendrocyte. Here we show that NMDA (N-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
463
2
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(486 citation statements)
references
References 26 publications
19
463
2
2
Order By: Relevance
“…Expression of AMPA/kainate receptors is particularly marked in immature cells of the oligodendrocyte lineage (Itoh et al, 2002), which in the neonatal optic nerve are in the process of forming an exquisitely close morphological arrangement with neighbouring axons (Butt and Ransom, 1993). We and others have recently demonstrated the presence of functional NMDA-type glutamate receptors in oligodendrocyte processes (Salter and Fern, 2005;Káradóttir et al, 2005;Micu et al, 2006)). The activation of these receptors is likely to be important in a variety of diseases and must have significant developmental consequences.…”
Section: Discussionmentioning
confidence: 96%
“…Expression of AMPA/kainate receptors is particularly marked in immature cells of the oligodendrocyte lineage (Itoh et al, 2002), which in the neonatal optic nerve are in the process of forming an exquisitely close morphological arrangement with neighbouring axons (Butt and Ransom, 1993). We and others have recently demonstrated the presence of functional NMDA-type glutamate receptors in oligodendrocyte processes (Salter and Fern, 2005;Káradóttir et al, 2005;Micu et al, 2006)). The activation of these receptors is likely to be important in a variety of diseases and must have significant developmental consequences.…”
Section: Discussionmentioning
confidence: 96%
“…N-methyl-D-aspartate (NMDA) glutamate receptors mediate Ca 2 þ accumulation in central myelin in response to chemical ischemia in vitro. 5 A prolonged activation of these receptors leads to increased intracellular concentrations of sodium, potassium and/or calcium ions. These changes in ionic gradients initiate a sequence of events that ultimately lead to cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely in periventricular white matter of neonatal rat, hypoxia-ischemia produces a significant depletion of oligodendroglial glutamate indicative of net release (Back et al, 2006), while in cell culture these cells release glutamate that can activate receptors on the host cell and its neighbours resulting in acute injury (Fern & Moller, 2000). The significance of NMDA (Karadottir et al, 2005;Salter & Fern, 2005;Micu et al, 2006) and non-NMDA (McDonald et al, 1998;Fern & Moller, 2000;Follett et al, 2000) glutamate receptors for oligodendroglia injury has been confirmed in a variety of preparations, but the significance of glutamate release from oligodendroglial cells themselves vs., release from astrocytes or axons (Kukley et al, 2007;Ziskin et al, 2007;Alix et al, 2008;Arranz et al, 2008) is not clear.…”
Section: Figure 2 Near Herementioning
confidence: 99%
“…Astrocytes are also replete with glutamate sensors such as ionotropic and metabotropic glutamate receptors (see Gallo & Ghiani, 2000), and are decorated with potential glutamate release mechanisms. While the physiological function(s) of glutamate release and reception in astrocytes is a matter of debate, it is clear that excessive glutamate release is associated with injury in disease states ranging from ischemic lesions such as stroke (see Hazell, 2007) including white matter injury (Karadottir et al, 2005;Salter & Fern, 2005;Micu et al, 2006), through demylinating disorders like multiple sclerosis (Pitt et al, 2000) to dementias such as Alzheimer's and Huntington's diseases (see Mattson, 2008). The acute injury associated with excess glutamate release is mediated by a well-characterized excitotoxic cascade involving synaptic exocytosis, depolarization and further synaptic release.…”
Section: Glutamate Releasementioning
confidence: 99%